Promoting Healthy Lifestyles Among Older Cancer Survivors to Improve Health and Preserve Function - Demark-Wahnefried, Wendy (2009)
Currently, there are almost 7 million cancer survivors in this country who are age 65 years or older, and this number is expected to rapidly increase given trends toward aging and improvements in early detection and treatment. Unfortunately, cancer survivors are at risk for several comorbid conditions and accelerated functional decline. In a previous cross-sectional study among 688 older breast and prostate cancer survivors, we found significant associations between lifestyle practices and levels of physical functioning, with positive associations noted for physical activity, and fruit and vegetable consumption, and negative associations observed for dietary fat. In a more recent cross-sectional study among 753 older survivors of breast, prostate and colorectal cancer, we continued to observe significant associations between physical function, and physical activity (ρ=0.22, p<0.0001) and diet quality (ρ=0.07, p=0.046), and also found a significant negative association between physical function and body mass index (ρ=− 0.29, p<0.0001). Therefore, speculation exists that lifestyle interventions may be helpful in positively reorienting the trajectory of functional decline in this vulnerable population; however, there are substantial barriers, such as travel, that must be overcome in delivering behavioral interventions to older cancer survivors. Previously reported results from our Pepper Center-funded Project LEAD (Leading the Way in Exercise and Diet) intervention development study, suggested that an exercise and diet intervention delivered via telephone counseling and mailed materials was readily accepted and appeared to be of benefit. Larger trials, such as Reach-out to ENhancE Wellness in Older Survivors (RENEW) are currently underway and should soon yield results.